Multi-user virtual environments for teaching and learning in higher education: perspectives from students and teachers using second life - Penfold, Paul (Journal of Technical Education Science, 2011)
Academic institutions are facing many challenges, not least, how to handle and manage the education of students brought up in the digital age. This paper describes the experience of students and teachers from one Hong Kong university that used Second Life – a Multi-User Virtual Environment (MUVE) – for teaching four pilot courses from a hospitality and tourism curriculum. The study reviews virtual environments and the use of Second Life in teaching and learning in higher education. It considers the type of activities used in the MUVE for hospitality and tourism studies – role play simulation, virtual lectures, room design and virtual field trips. The findings set out the students’ perceptions of using the MUVE and teachers views on using Second Life. The study discusses challenges and problems faced – the learning curve involved and technology issues and support, as well as the benefits of using the virtual environment Students were asked what difficulties they experienced in using Second Life across eight dimensions on a 5-point Likert Scale. Students indicated that they found the initial set up, registration, and installation more difficult than using an avatar and working in Second Life. The seven major challenges faced by most teachers and students were technology, support, faculty development, legal issues, mature content, learning curve and cost. Teachers saw the most important benefits of Second Life as those related to their ability to provide students with more interactivity and enjoyment of their learning experience, as well as the variety added to the teaching. Feedback from students and teachers in this initial trial of Second Life indicated that both groups found their experience of using the MUVE to be positive and beneficial to learning. Our conclusions here are that generally students find Second Life fun to use; it arouses their learning interest and provides an interactive experience. When the technical issues are minimized, and students and teachers are well prepared for class, then it is a very positive medium to enhance learning and provide more interactive and enjoyable learning experiences for students and teachers